2021
DOI: 10.3390/app11104378
|View full text |Cite
|
Sign up to set email alerts
|

Wikidata Support in the Creation of Rich Semantic Metadata for Historical Archives

Abstract: The research question this paper aims at answering is the following: In an ontology-driven annotation system, can the information extracted from external resources (namely, Wikidata) provide users with useful suggestions in the characterization of entities used for the annotation of documents from historical archives? The context of the research is the PRiSMHA project, in which the main goal is the development of a proof-of-concept prototype ontology-driven system for semantic metadata generation. The assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While reviewing the literature, it was found that the majority of existing research focuses on either technological aspects or ontological aspects of the platform. More Specifically, review of the literature illustrated that researchers use Wikidata to conduct new types of research (Amaral et al, 2021;Colla et al, 2021;Ferradji & Benchikha, 2021;Good et al, 2016;Kaffee, 2016;Konieczny & Klein, 2018;Lemus-Rojas & Odell, 2018;Li et al, 2022;Meier, 2022;Mietchen et al, 2015;Morshed, 2021;Neelam et al, 2022;Rasberry & Mietchen, 2021;Shenoy et al, 2022;Taveekarn et al, 2019;Waagmeester et al, 2020Waagmeester et al, , 2021Zhang et al, 2022). Researchers also use Wikidata to conduct new types of academic analysis in a variety of disciplines (Arnaout et al, 2021;Burgstaller-Muehlbacher et al, 2016;Kaffee et al, 2017;Klein et al, 2016;Lemus-Rojas, n.d.;Pfundner et al, 2015;Putman et al, 2017;Rutz et al, 2021;Scharpf et al, 2021a, b;Turki et al, 2019Turki et al, , 2022a.…”
Section: Wikidata Users and Early Adoptersmentioning
confidence: 99%
“…While reviewing the literature, it was found that the majority of existing research focuses on either technological aspects or ontological aspects of the platform. More Specifically, review of the literature illustrated that researchers use Wikidata to conduct new types of research (Amaral et al, 2021;Colla et al, 2021;Ferradji & Benchikha, 2021;Good et al, 2016;Kaffee, 2016;Konieczny & Klein, 2018;Lemus-Rojas & Odell, 2018;Li et al, 2022;Meier, 2022;Mietchen et al, 2015;Morshed, 2021;Neelam et al, 2022;Rasberry & Mietchen, 2021;Shenoy et al, 2022;Taveekarn et al, 2019;Waagmeester et al, 2020Waagmeester et al, , 2021Zhang et al, 2022). Researchers also use Wikidata to conduct new types of academic analysis in a variety of disciplines (Arnaout et al, 2021;Burgstaller-Muehlbacher et al, 2016;Kaffee et al, 2017;Klein et al, 2016;Lemus-Rojas, n.d.;Pfundner et al, 2015;Putman et al, 2017;Rutz et al, 2021;Scharpf et al, 2021a, b;Turki et al, 2019Turki et al, , 2022a.…”
Section: Wikidata Users and Early Adoptersmentioning
confidence: 99%
“…Research on resolving or improving digital archives using Wikidata has recently emerged (Kapsalis, 2019). Colla et al (2021) introduced a method of recommending new entities for digital materials by using named entities extracted from Wikidata. Previous research on archival metadata using knowledge graphs has typically focused on how existing vocabularies can be used to describe archival materials and enable improved discovery and access to these materials through the Web (Hawkins, 2022).…”
Section: Knowledge Graph For Digital Archivesmentioning
confidence: 99%
“…There has been much work on digitizing and publishing data about cultural heritage collections, for example through an integrative semantic portal (Hyvönen et al, 2005), through translation of cultural heritage metadata into linked open data (Haslhofer et al, 2011;De Boer et al, 2012;Matsumura et al, 2012;Knoblock et al, 2017) and through the development of specialist ontologies and knowledge bases (Schmitz and Black, 2008;Brownlow et al, 2015;Carriero et al, 2019). Other works on digitizing museum-related information include sharing of museum visit experiences via web and smartphone apps, digital bookmarking, or real-time video (Kostoska et al, 2013;Pisoni et al 2020), digitization of historical archives (Colla et al, 2021), and application of machine-learning approaches to automatically generate cultural heritage content or metadata utilising public resources such as Wikipedia and Wikidata (De Benedictis et al, 2021;Colla et al, 2021). In contrast to such works, the MM project aims to support experts' research into the history, status and development of a whole museum sector.…”
Section: Related Workmentioning
confidence: 99%